Zapisz wyrażenia, nie uzywając nawiasów. Zredukuj wyrazy podobne.
a)x+(3x-y²+7)
b)-a+(2a-3b-1)
c)-x²+(x²-x-7)
d)-b³-(b³-b²-b)
e)(2a-3b)+(4a-b)
f)-(x²-3x)+(x²+3x)
g)(a+b-c)-(2a-b+2c)

proszę o rozpisanie pilne musze miec to dzisiaj
prosze pomóżcie

2

Odpowiedzi

Najlepsza Odpowiedź!
2009-12-10T20:48:15+01:00
A)x+(3x-y²+7)=x+3x-y²+7=4x-y²+7
b)-a+(2a-3b-1)=-a+2a-3b-1=a-3b-1
c)-x²+(x²-x-7)=-x²+x²-x-7=-x-7
d)-b³-(b³-b²-b)=-b³-b³+b²+b=-2b³+b²+b
e)(2a-3b)+(4a-b)=2a-3b+4a-b=6a-4b
f)-(x²-3x)+(x²+3x)=-x²+3x+x²+3x=6x
g)(a+b-c)-(2a-b+2c)=a+b-c-2a+b-2c=-a+2b-3c
1 5 1
2009-12-10T20:55:41+01:00
A) x+ (3x-y²+7)= x+ 3x-y²+7=-y²+4x+7
b) -a + (2a-3b-1)=-a+2a-3b-1=a-3b-1
c) -x²+(x²-x-7)=-x²+x²-x-7= -x-7
d) -b³- (b³-b²-b)=-b³-b³+b²+b= -2b³+b²+b
e) (2a-3b)+ (4a-b)= 2a - 3b+4a-b=6a-4b
f) -(x²-3x) + (x²+3x)= -x² + 3x+x²+3x= 6x
g) (a+b-c) - (2a-b+2c)= a+b-c-2a+b-2c= -a+2b-3c